Strategi Pemberdayaan Sentra Industri Konveksi Dalam Upaya Meningkatkan Kesejahteraan Masyarakat Di Desa Tritunggal Kecamatan Babat Kabupaten Lamongan - Putri Maisarohtussa’diyah; Muhammad Ridwan Basalamah; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The strategy for empowering the convection industry center in an effort to improve the welfare of the people in Tritunggal Village is as well as empowering the convection industry center to improve people's welfare, through human resources in the environment around Tritunggal Village. Tritunggal Village, Babat District, Lamongan Regency is one of the locations with quite a lot and adequate convection industrial centers. With a total of 154 convection industry businesses as of February 24 2022, as well as the production of children to adult clothing, uniforms, screen printing and embroidery that have been made or received to order. Focusing on the middle-class convection industry center named "Jaya Makmur" owned by "Ahmad Rosyidi" and the Home Industry-scale convection industry center named "WWC Collection" owned by "Wahyu Widodo". Therefore, with the existence of sufficient industrial centers, it is the main focus in research that aims to find out and describe the strategies, constraints, and benefits or role of empowering the convection industry center in an effort to improve people's welfare in Tritunggal Village, Tritunggal District, Lamongan Regency. . By using qualitative research methods through observation, interview and documentation techniques, with key informant participants, supporting informants and evaluator informants, as was done in Tritunggal Village with a predetermined period of time. So that the strategy applied to each convection has its own characteristics and characteristics, through the creativity and innovation of each owner to maintain and develop the convection industry center in its market segment, as the "Jaya Makmur" industrial center has a focus on Embroidery, while the convection industry center "WWC Collection" has a focus on screen printing to produce a product. Each industrial center also has constraints on its own scale or market segment, as the middle-class industrial center "Jaya Makmur" has constraints in technology, which is increasing year by year as the age of the technology used increases, so it requires maintenance and even changes in technology as needed. Meanwhile, the constraints faced by the convection industry center for the "WWC Collection" Home Industry class are one's interest in working in the realm of screen printing, price competition, and quality to maintain the industry in its market segment. Meanwhile, the benefits generated by each convection industry center have a positive impact, especially for the people of Tritunggal Village and its surroundings to support the economy and individual living standards, thereby increasing people's welfare. Keywords: Empowerment Strategy, Convection Industry Center, Community Welfare.